POTENSI INTEGRASI ZAKAT DAN WAQAF BERBASIS DIGITAL UNTUK PENCAPAIAN SUSTAINABLE DEVELOPMANT GOALS (SDGS) DALAM PRESPEKTIF MAQASHID SYARIAH - Fajar Satriyawan Wahyudi; Azrul Amirullah, Muhammad (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
This study examines the potential of digital-based zakat and waqf integration as a strategic instrument to support the achievement of the Sustainable Development Goals (SDGs) through the Maqashid Sharia approach. Using descriptive qualitative methods and literature studies, this study explores how digitalization can improve efficiency, transparency, and inclusiveness in zakat and waqf management. The analysis shows that digital zakat and waqf integration aligns with the five main objectives of Maqashid Sharia, namely the protection of religion, life, intellect, descendants, and property. Digital transformation is a catalyst for increasing public participation and equitable distribution of benefits, as well as addressing sustainable development challenges such as poverty, social inequality, and access to education. However, the implementation of this integration still faces challenges, including low digital literacy, a lack of innovation in social financial products, and limitations in regulations and reporting systems. Therefore, synergy between Islamic financial institutions, the government, and stakeholders is needed to build an adaptive, accountable, and sustainable zakat and waqf governance system to strengthen Islam's contribution to global development.